2017
DOI: 10.3201/eid2308.161971
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Evidence of Powassan Virus Infection in Patients with Suspected Lyme Disease1

Abstract: Powassan virus (POWV) lineage II is an emerging tickborne flavivirus with an unknown seroprevalence in humans. In a Lyme disease–endemic area, we examined the seroreactivity to POWV in 2 patient cohorts and described the clinical features of the POWV-seroreactive patients. POWV disease might be less neuroinvasive than previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 12 publications
(19 reference statements)
0
26
0
Order By: Relevance
“…One study reported the occurrence of Anaplasma phagocytophilum coinfection in one out of three patients with POWV encephalitis (137). In another study, among 41 patients with evidence of Borrelia burgdorferi infection, 7 (17.1%) showed serological evidence of acute POWV infection, and 3 (7.3%) had laboratory-confirmed POWV infection (167). In a case series analysis, which processed data from 14 patients hospitalized with POWV encephalitis, 2 patients (14.2%) with erythema migrans had detectable antibodies to Borrelia burgdorferi (178).…”
Section: Clinical Disease and Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…One study reported the occurrence of Anaplasma phagocytophilum coinfection in one out of three patients with POWV encephalitis (137). In another study, among 41 patients with evidence of Borrelia burgdorferi infection, 7 (17.1%) showed serological evidence of acute POWV infection, and 3 (7.3%) had laboratory-confirmed POWV infection (167). In a case series analysis, which processed data from 14 patients hospitalized with POWV encephalitis, 2 patients (14.2%) with erythema migrans had detectable antibodies to Borrelia burgdorferi (178).…”
Section: Clinical Disease and Diagnosismentioning
confidence: 99%
“…Seroprevalence rates ranged between 0 and 5.8% among residents of Ontario in the late 1950s and 1960s, showing variation among communities, a finding that suggested a focal occurrence of both tick vectors and POWVs (141,164,165). In seroepidemiological studies conducted later among residents in British Columbia, New York, Minnesota, and Wisconsin, 6.1%, 0.7%, 4%, and 4% of individuals, respectively, had POWV antibodies in their sera (147,163,166,167). These data from areas of endemicity are consistent with the hypothesis that many infections remain undetected due to absent or mild symptoms.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In 1968–1969, a sample of outdoor workers in British Columbia, Canada had a seroprevalence rate of 12.4% (Kettyls et al., ). Two recent studies conducted in Wisconsin, USA reported seroprevalence rates of 9.5% on a sample of patients with suspected Lyme disease (Frost et al., ) and 10.4% on another sample of patients with suspected tick‐borne disease (Schotthoefer et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Coinfections with POWV and B. burgdorferi (El Khoury, Camargo, White, et al., ; Frost et al., ; Schotthoefer et al., ), Escherichia coli (El Khoury, Hull, et al., ), Saint Louis Encephalitis virus (Raval et al., ) and Anaplasma phagocytophilum (Johnson et al., ) were reported in six studies. Eight studies noted comorbidities of POWV patients including cerebral aneurysm (Birge & Sonnesyn, ), chronic obstructive pulmonary disease (El Khoury, Hull, et al., ), Crohn's disease (Piantadosi et al., ), colon cancer (Birge & Sonnesyn, ; Raval et al., ), coronary artery disease (Piantadosi et al., ), cutaneous lupus (Birge & Sonnesyn, ), diabetes (El Khoury, Hull, et al., ; Raval et al., ), hyperlipidaemia (El Khoury, Hull, et al., ), hypertension (Birge & Sonnesyn, ; El Khoury, Hull, et al., ; Piantadosi et al., ; Raval et al., ), immunocompromised (Minnesota Department of Health, , ), leukaemia (El Khoury, Camargo, White, et al., ), lymphoma (Piantadosi et al., ; Raval et al., ), prostatitis (El Khoury, Hull, et al., ) and psoriatic arthritis (Piantadosi et al., ).…”
Section: Resultsmentioning
confidence: 99%